Heart rate response and chronotropic incompetence in exercise stress testing of asymptomatic women. (November 2010) - Mansur, Alfredo Jose; Nunes, Rafael Amorim Belo
Evaluation of: Gulati M, Shaw LJ, Thisted RA, Black HR, Bairey Merz CN, Arnsdorf MF: Heart rate response to exercise stress testing in asymptomatic women: The St. James Women Take Heart Project. Circulation 122, 130–137 (2010). Peak heart rate achieved with exercise in 5437 asymptomatic women submitted to symptom-limited exercise stress testing demonstrated an inverse relationship with increasing age, expressed by 206-0.88(age), which is lower than the traditional estimate of 220-(age). A nomogram was derived. This new formula for estimating peak heart rate during exercise and the derived chronotropic incompetence was found to be a more accurate predictor of all-cause mortality in this study sample.